2020
DOI: 10.1002/cncr.32757
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life among breast cancer survivors and noncancer controls over 10 years: Pink SWAN

Abstract: BACKGROUND:The goal of this study was to compare health-related quality of life (HRQL) from diagnosis to 10 years postdiagnosis among breast cancer survivors (BCS) and women without cancer over the same period and to identify BCS subgroups exhibiting different HRQL trajectories. METHODS: Our analysis included 141 BCS and 2086 controls from the Study of Women's Health Across the Nation (SWAN), a multiracial/ethnic cohort study of mid-life women assessed approximately annually from 1995 to 2015. Pink SWAN partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 40 publications
(113 reference statements)
4
21
2
Order By: Relevance
“…Intense BC treatments can induce many side effects over the cancer trajectory, which could explain the decline that also occurred in the physical aspects of HRQoL at one year post diagnosis. Lower levels of HRQoL in BC patients compared to the population norms have been demonstrated in previous studies [ 11 , 36 ], but studies exploring resilience in relation to HRQoL are limited. Despite differences in the HRQoL instruments, our findings are in agreement with the results reported by Ristevska-Dimitrovska et al, Zhang et al, and Tu et al, demonstrating that the levels of resilience are positively related to the levels of HRQoL in BC patients [ 8 , 9 , 16 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Intense BC treatments can induce many side effects over the cancer trajectory, which could explain the decline that also occurred in the physical aspects of HRQoL at one year post diagnosis. Lower levels of HRQoL in BC patients compared to the population norms have been demonstrated in previous studies [ 11 , 36 ], but studies exploring resilience in relation to HRQoL are limited. Despite differences in the HRQoL instruments, our findings are in agreement with the results reported by Ristevska-Dimitrovska et al, Zhang et al, and Tu et al, demonstrating that the levels of resilience are positively related to the levels of HRQoL in BC patients [ 8 , 9 , 16 ].…”
Section: Discussionmentioning
confidence: 92%
“…High-resilience patients will more effectively manage their new life situations [ 3 ]. Due to its favorable survival rate, HRQoL has become an important outcome measure for BC patients [ 10 , 11 ], and by adding resilience, it might be possible to predict HRQoL and to identify those most in need of additional rehabilitation interventions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, regarding the more specific subscales, BC survivors reported higher levels of symptoms, e.g., fatigue and dyspnea, as well as larger deficits in role, emotional, social and cognitive functioning [17][18][19][20][21]. Other studies used the 36-item Short-Form Health Survey (SF-36) questionnaire [22] and likewise found impairment in HRQoL in BC survivors compared to the reference populations [23][24][25][26]. It should be noted in one study, differences where moderated by time since diagnosis with the largest differences closest to diagnosis [24], and in two other studies differences between BC survivors and control groups were only found one year postdiagnosis with follow-up periods of respectively two years and ten years [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Two cross-sectional studies reported that HRQoL approached the level of the general population or controls without cancer after approximately five years [4,25]. Several longitudinal studies with longer follow-up periods extending up to ten years post-diagnosis, however, have reported that a new downward shift in HRQoL was seen after an initial improvement in the first years and that survivors had lower HRQoL, more symptoms, and decreased functions even ten or more years after treatment [2,3,27,28]. A delayed decline in HRQoL might reflect late effects resulting from cancer and its treatment, such as cardiac, respiratory, or musculoskeletal problems that may appear more than five years after treatment [29,30].…”
Section: Discussionmentioning
confidence: 99%